Wear characteristics of sintered AA2014 with alumina and titanium di-Boride metal matrix composites. Issue 2 (25th January 2021) - Jayavelu, S.; Mariappan, R.; Rajkumar, C.
ABSTRACT: The present research work deals with the fabrication of the AA2014 aluminum alloy and two aluminum metal matrix composites such as composite-I (95 wt % AA2014 + 5 wt% of Al2 O3) and composite-II (95 wt % AA2014 + 5 wt% of TiB2) through the powder metallurgy route. Elemental powders of the AA2014 aluminum alloy, composite-I and composite-II were compacted at a pressure of 350 ± 10 MPa using the universal testing machine and sintered at 610 ± 10° C for 2 h in a vacuum hot press under nitrogen atmosphere. Compositions were considered for micro structural, density, porosity, mechanical properties and wear analysis. Microstructural analysis reveals the uniform distribution of reinforcement particle with cluster formation. In the density analysis, the sintered AA2014 aluminum alloy has exhibited 95% of its theoretical density. The AA2014 aluminum alloy shows less porosity compared with composite-I and composite-II. Composite-II exhibits higher wear resistance and lower coefficient of friction which will lead to cost saving and increases engine efficiency.